2012
DOI: 10.1103/physrevc.86.015212
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian analysis of kaon photoproduction with the Regge-plus-resonance model

Abstract: We address the issue of unbiased model selection and propose a methodology based on Bayesian inference to extract physical information from kaon photoproduction p(γ, K + )Λ data. We use the single-channel Regge-plus-resonance (RPR) framework for p(γ, K + )Λ to illustrate the proposed strategy. The Bayesian evidence Z is a quantitative measure for the model's fitness given the world's data. We present a numerical method for performing the multidimensional integrals in the expression for the Bayesian evidence. W… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 96 publications
1
54
0
Order By: Relevance
“…Similar approaches have previously been proposed in the literature in different contexts [68][69][70][71]. In particular, the so-called Regge-plus-resonance (RPR) model developed by the Ghent group was used with remarkable success in photoproduction of strange hadrons [72][73][74]. However, due to the important differences between the RPR model and the present approach, we refer to the latter as Hybrid model.…”
Section: From Low To High Invariant Masses: Hybrid Modelmentioning
confidence: 97%
“…Similar approaches have previously been proposed in the literature in different contexts [68][69][70][71]. In particular, the so-called Regge-plus-resonance (RPR) model developed by the Ghent group was used with remarkable success in photoproduction of strange hadrons [72][73][74]. However, due to the important differences between the RPR model and the present approach, we refer to the latter as Hybrid model.…”
Section: From Low To High Invariant Masses: Hybrid Modelmentioning
confidence: 97%
“…In Refs. [72,73], the most probable resonance content (Bayesian evidence) is determined considering kaon photoproduction. Bayesian priors have also been used to restrict the low-energy constants in effective field theories to natural values and estimate the truncation errors [74,75].…”
Section: Introductionmentioning
confidence: 99%
“…The interest in this state has increased since it was shown in [32] that this state was an ideal candidate to explain the peak around 1920 MeV observed in the γp → K + Λ reaction. It has been quite rewarding to see that in a recent work using Bayesian statistics to determine the most probable combinations of resonances needed to describe the γp → K + Λ reaction [33,34], a N * , J P = 1/2 + state with mass around 1900 MeV is needed to best explain the data.…”
Section: Three Body Systems Involving Kaonsmentioning
confidence: 99%
“…Yet, the atoms studied in these former works correspond to orbits with l equal or bigger than one, and one can rightly ask where are the states with l = 0. The answer to this problem was given in [3] where it was found that, based on potentials derived from chiral unitary theory [4], those states are deeply bound, by [30][31][32][33][34][35][36][37][38][39][40] MeV, but the width is about 100 MeV, which sets clear limits to their experimental observability. One must also quote that there are different claims, with larger bindings and narrower widths, based on phenomenological potentials fitted to data of kaonic atoms [1].…”
Section: Introductionmentioning
confidence: 99%